Amorphous solid dispersion to enhance the bioavailability of poorly soluble drug - Tee, Hui Shi (Nanyang Technological University, 2023)
Due to their unique qualities such as biocompatibility, ability to be tuned to suit different drugs and stability, deep eutectic solvents (DESs) have drawn more focus in the last ten years. In the pharmaceutical business, DESs have shown potential to effectively fabricate drugs to be more solvable and attain better penetration, both of which are essential for drug absorption and efficacy. Because of this, DESs have recently gained widespread and useful acceptance as adaptable drug delivery systems for a variety of administration routes with improved bioavailability. Their ability to increase drug dissolution offers a promising solution to many poorly soluble drugs such as ibuprofen. In this study, a therapeutic DES (THEDES) based on ibuprofen and menthol was synthesised and mixed with polyvinylpyrrolidone (PVP K30) as the polymer matrix to form amorphous solid dispersion (ASD). The payload of ibuprofen was analysed by high-performance liquid chromatography (HPLC). X-ray powder diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) spectra confirmed that an amorphous state was achieved. The results from dissolution and supersaturation tests indicate that the THEDES does have improved solubility as compared to its constituent elements. These results obtained will provide the basis for further work to identify the mechanisms involved behind the behaviour of DESs properties and improve the solubility and stability of ibuprofen.